2011
DOI: 10.1038/ijo.2011.64
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing trends in overweight and obesity among an Australian population of preschool children

Abstract: Background: After several decades of increasing prevalence, recent evidence suggests a levelling of obesity rates in some groups, although little is known about trends in children under 5 years of age. Aim: To investigate the prevalence, trends and sociodemographic correlates of overweight and obesity in Australian preschool children between 1999 and 2007. Methods: Child anthropometric and demographic data were extracted from records of routine maternal and child health consultations for children aged 2 and 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
3
30
1
3
Order By: Relevance
“…In fact, a small but significant decline in the combined rate of overweight and obesity between 2001/02 to 2009/10 was observed. This decrease is similar to that reported for children in several other countries including Australia, Denmark, France, Germany, Sweden, the United Kingdom and the United States [5][6][7][8][9][10] and in Canada for older children. 23 Stabilization of the prevalence of overweight and obesity was found among boys and girls.…”
Section: Discussionsupporting
confidence: 72%
“…In fact, a small but significant decline in the combined rate of overweight and obesity between 2001/02 to 2009/10 was observed. This decrease is similar to that reported for children in several other countries including Australia, Denmark, France, Germany, Sweden, the United Kingdom and the United States [5][6][7][8][9][10] and in Canada for older children. 23 Stabilization of the prevalence of overweight and obesity was found among boys and girls.…”
Section: Discussionsupporting
confidence: 72%
“…Most countries have experienced an increased prevalence of overweight and obesity during the past few decades [14,11], but recent data suggest that the prevalence has stabilized or even decreased, as observed in Australia, the US and several European countries [5,810]. With the results of this study based on Danish data, we contribute to the growing evidence of the levelling off in the prevalence of overweight and obesity among children and adolescents that now seems to be occurring simultaneously in many parts of the world [5].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood overweight and obesity rates continue to rise in some countries like Mexico, India, China, Canada and Vietnam [5,6], but within the last decades the prevalence has plateaued in several European countries, in the US and in Australia [5,7,8]. Some studies have even reported a decrease in the prevalence [5,9,10]. In Denmark, the picture has been similar with an increase followed by a levelling off from year 2000 and onwards in the prevalence of childhood overweight and obesity [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of socioeconomic status as an independent determinant or mediator of behaviour further adds intricacy to our understanding of obesity and related behaviours [16,17]. Some studies suggest that family food security level and its output as well as the child’s health are antecedents of childhood obesity [8].…”
Section: Introductionmentioning
confidence: 99%